Data-Driven process discovery and analysis : Second IFIP WG 2.6, 2.12 International Symposium, SIMPDA 2012, Campione d'Italia, Italy, June 18-20, 2012, Revised Selected Papers - Ceravolo, Paolo; Gasevic, Dragan; Cudre-Mauroux, Philippe (Lecture Notes in Business Information Processing, 2013)
This book constitutes the thoroughly refereed proceedings of the Second International Symposium on Data-Driven Process Discovery and Analysis held in Campione d'Italia, Italy, in June 2012. The six revised full papers were carefully selected from 17 submissions. To improve the quality of the contributions the symposium fostered the discussion during the presentation, giving authors the opportunity to improve their work extending the presented results. The selected papers cover topics spanning from theoretical issues related to process representation, discovery and analysis to practical and operational experiences in process discovery and analysis.